Miłośnicy zegarków i zegarów - ich wizerunek i tożsamość w Internecie = Clock and Watches Enthusiasts Club - Their Picture and Identity in the Internet - Kładoczny, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes group of clock and watches enthusiasts focused near internet forum concerning clocks. They create scattered population, which are connected the common interest. A part of them join to the association Clock and Watches Enthusiast Club. It is able to know many informations about members by subforum webside "Let`s inroduce" ("Przedstawmy się").
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie